BALANCING CUSTOMER AND COMPETITOR IN MARKETING ORIENTATION: A CASE STUDY AT GENERAL COMPANY FOR IRAQI AIRWAYS - Rounaq Kadhem Hussin Shuba; Sarmad Hamza Jassim (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Companies generally face difficulty in accurately diagnosing their marketing orientation that may be customer-centered company and competitor-centered company, which is a field problem that this research is trying to find an appropriate solution by designing a checklist that suits this purpose. General Company for Iraqi Airways has be chosen as a sample for the research because of its significant in the transportation industry, some results have been reached that marketing orientation of company are customer- centered and competitorcentered in varying proportions at the same time. The research proposes to the company some steps that identify its marketing orientation and help it achieve a balancing between it be the customer-centered and be the competitor-centered in a way that company ensures achieving goals efficiently.